Efficacy and safety of valsartan and amlodipine single-pill combination in hypertensive patients (PEAK study) - Pınar Kızılırmak; Mehmet Berktaş; Mehmet Rıdvan Yalçın; Bülent Boyacı (KARE Publishing, 2013)
Objectives: This study was designed to assess the safety, compliance and efficacy of amlodipine (Aml) and valsartan (Val) single-pill combination (SPC) in a large hypertensive patient population. Study design: This is a non-interventional, observational, open label study conducted in 166 centers in Turkey with a 24-week follow-up period. Results: Of the 1184 enrolled patients, two-thirds were female (62.2%). The mean age was 57.7+-11.3 years, and 26.1% of the patients were older than 65 years. The majority of patients (82.3%) were overweight or obese. During the course of the study, 150 (12.7%) patients experienced a total of 174 adverse events (AEs). The overall mean (SD) compliance rate was determined to be 96.9 (0.2)%. The most commonly reported AE was edema, with a new-onset edema incidence of 6.7%. In the entire group, Aml/Val SPC significantly reduced both systolic and diastolic blood pressure (BP), with a reduction of 29.6+-0.9 / 14.7+-0.6 mmHg (for each, p<0.001). Conclusion: As a result of the low incidences of AEs and new-onset edema, the safety profile of Aml/Val SPC proved to be optimal. Aml/Val SPC reduced BP efficiently and met the needs of most patients to achieve the targets. Aml/Val SPC seems to be a beneficial option for effective BP control, which is a key factor influencing cardiovascular outcome.